Controlled volatile release of structured emulsions based on phytosterols crystallization. (May 2016) - Chen, Xiao-Wei; Guo, Jian; Wang, Jin-Mei; Yin, Shou-Wei; Yang, Xiao-Quan
Abstract: Flavor is one of the most important criteria for consumer acceptance of food products, especially for low-fat food emulsions. In this study, we prepared structured flavoring oil-in-water (O/W) emulsions based on the crystallization behavior of β -sitosterol (Sito), a functional phytosterol, in the presence of emulsifier (sodium caseinate, SC and octenylsuccinate starch, OSS), These structured emulsions improved colloidal stability during long-term storage and delayed volatiles release under real time dynamic condition. However, the equilibrium static headspace analysis did not show significant differences in the affinities of hydrophobic volatile compounds with pure constitutes of unstructured and structured emulsions. This highlighted the importance of structural properties of the O/W interface in volatile release modulation. A modified gel trapping technology (GTT) combined with polarized light microscopy (PLM) and confocal laser scanning microscope (CLSM) were applied to characterize the microstructure at the oil-water interface, and it clearly showed the formation of a novel Sito crystal/OSA starch complex interface for OSS stabilized structured emulsion. This unique interfacial microstructure might contribute to the strong retention of volatile compounds due to steric barrier and enhanced affinity to those lipophilic volatiles. The formulated flavor emulsion with controlled volatile release profile was successfully prepared by simply blending the unstructured and structured flavoring emulsions. This work provides indications for potential applications of the formulation design in flavor emulsions and phytosterols structured emulsion as novel aroma delivery systems to improve flavor perception. Graphical abstract: Highlights: A home-made double well jacketed glass cell was improved for real-time dynamic flavor release. Modified GTT combined with PLM and CLSM was to characterize the interfacial microstructure. Emulsions with Sito structured had improved the physical stability and volatile characteristics. Sito crystal/OSA starch complex interface worked to volatiles release.